Taxonomic Study of Monogenea Parasitic Worms on the Gills of Pagellus erythrinus in the Syrian Marine Waters. - لايقة , تغريد; سليم , ناريمان (Latakia University Journal -Biological Sciences Series, 2021)
The present study aimed to classify Monogenea's external parasites that infect the gills of Pagellus erythrinus fish. Fish samples were collected monthly during the period between 22/1/2019 and 8/12/2019 from different fishing areas. The total number of fish examined was 146 individuals. In this paper, the parasite Lamellodiscus elegans (Diplectanidae) was isolated from gills of Pagellus erythrinus with an infection rate of 87.67% and an infection severity (11.49) parasite / fish. The parasite Microcotyle sp. (Microcotylidae) with a percentage of (25.34)% and severity of infection (1.62) parasite / fish. Choricotyle sp. (Diclidophoridae) was present during spring with a percentage of only (0.68)% and a severity of infection (1) parasite / fish. This is the first time that these external parasites have been isolated from Pagellus erythrinus in the Syrian marine waters.